Intercom and video capture system / Mohd Hafizuddin Omar and Mohd Aziman Ahmed - Omar, Mohd Hafizuddin; Ahmed, Mohd Aziman (2005)
Intercom is literally a system that enables voice communication protocol between the persons from different part of a building, ship, airplane, and other place as long as it is within the designated range. Intercom is simply the merging of the words ‘inter’ and ‘com’. ‘Inter’ means to interact with each other between the units signified. ‘Com’ or communication means conveyance of information. There are several reasons that have seduced us in venturing into this part of the SMART HOME project. First of all, the present Intercom systems that are available to consumers are within the domain of extremely delusive price that is out of the consumers’ reach to obtain one. They have to pay exorbitantly in order to have it installed to their designated area. Here is where our project came into the picture. We are aiming at producing an intercom system that is fully operational, reliable, and most importantly of reasonable price that is attractive to the consumer and competitive in the market of communication devices. Initially we have allotted about RM 400 for this project that covers the costs of the intercom and video capture system. After running further test, we found out that the prices can still be reduced by the quality of the components’ factor. Less quality components are likely to be cheaper. The intercom and video capture system can be primarily placed at the front door or from gate to the main monitoring system of the house, and from room to room. We can also use the intercom without the video capture accessory. The decision to install the accessory (video capture device) is up for the consumer to determine. The benefit of the project is two people can communicate from one place to another in the house, security in order to make our life easier and for the video capture system, the users at both ends can determine the identities of their respondent though visual recognition.